Deletion of p63 exon 13 in mice reveals C-terminal isoform–specific functions in epithelial development - Anna Maria Lena; Artem Smirnov; Mara Mancini; Manuela Montanaro; Fabiola Ciccosanti; Valeria Foti; Roberta Nardacci; Gian Maria Fimia; Mara Mavilio; Massimo Federici; Alessandro Mauriello; Mauro Piacentini; et al. (Proceedings of the National Academy of Sciences, 2025)
The transcription factor p63 is an essential regulator of epithelial development. Yet, the complexity at the 3′UTR, which gives rise to the three distinct C-terminal protein isoforms (α, β, and γ), remains unresolved and opens an investigation on the in vivo role of the C-terminus. This region, codified by exon 13, harbors genetic mutations leading to AEC syndrome. Here, we generated a mouse with a deletion of p63 exon 13 in keratin-14-expressing tissues and employed transcriptome, genome-wide occupancy, and interactome studies to characterize the role of the p63 C-terminus in vivo. In this model mouse, the p63 protein is expressed at the correct level in time and space but predominantly as the β isoform instead of the α isoform, thereby providing insights into the function of the C-terminus. We show that p63β interacts more readily with the core promoter transcription machinery and p63α-depleted isoforms bind more frequently the promoter region of target genes, resulting in inappropriate overexpression of extracellular matrix organization genes in the skin. This leads to the aberrant adhesion of epidermal keratinocytes to the basal lamina and triggers systemic inflammation, growth abnormalities, and premature death. We found a significant role of the full-length ΔNp63a isoform which cannot be substituted by the other isoforms (β or γ). Our studies highlight a crucial role for p63α in correctly orchestrating the gene expression program to ensure proper formation of epithelia.